PENERAPAN MOTIF ARABES MASJID MANTINGAN SEBAGAI UNSUR ESTETIKA PADA WALL FOLDING DESK - Erisa, Dian; Sany, Nukhbah; Budiarto, Budiarto (Universitas Mercu Buana, 2023)
Indonesia has a wide variety of art crafts, one example is carving. Art in the form of carving can be found in Jepara Regency, known internationally for its beautiful quality. History records that Jepara carving began in the 16th century which can be seen in the ornaments of the Mantingan Mosque. The purpose of this research is to apply one of the Mantingan Mosque ornaments, namely arabesque motif, as an aesthetic element on a wall folding desk furniture. The wall folding desk is chosen for its multifunctionality, therefore can act as an alternative choice for homes or spaces with limited sizes. This wall folding desk furniture is equipped with lights, electrical terminals, and storage boxes as an effort to meet consumer needs. The product design process of this research refers to a qualitative approach using the design thinking method. The results of this study are in the form of product designs, technical drawings, and wall folding desk furniture products that apply the arabesque motif of the Mantingan Mosque. The expected benefits of this research are in the form of perseverance effort of the arabesque motif of the Mantingan Mosque as the forerunner of Jepara carving and the additional aesthetic value of the application of the Arabes motif of the Mantingan Mosque of the product.